COST OF DEBT AND DIVIDEND POLICY: EVIDENCE FROM MENA REGION - Jabbouri, Imad; Satt, Harit; Farooq, Omar (European Scientific Journal, ESJ, 2014)
Prior literature documents a positive relationship between dividend policy and corporate governance, and negative relationship between the quality of corporate governance and cost of debt. Therefore, we hypothesize that there is a negative relationship between cost of debt and dividend policy. Using a sample of firms from the MENA region (Middle East and North Africa), during the period between 2004 and 2008, we document a negative relationship between cost of debt and dividend policy. Our results remain robust even after controlling for various firm-specific characteristics. The main reason for this negative relationship is that dividend policy act as a substitute for corporate governance mechanisms in emerging markets. Prior literature argues that creditors take into consideration the quality of corporate governance while assessing the riskiness of the firm. High dividend payout ratio reflects proper corporate governance, which would result in a lower required rate of return by creditors, a lower cost of debt for the firm.